The four friends - Robbins: Rita (Jamaica Mind to Mind, 2016)
A deer, a mouse and a crow were very good friends. One day, while taking a walk, they met a tortoise. This book is printed in large print and beautiful page design. Read till the last page and learn the moral values behind this story.